Feasibility of using Nanofiltration membranes to delay Reverse Osmosis membrane fouling and to reduce energy consumption (BWC desalination plant) - Mourad Berrabah; Khadidja Benyahia; Ahlem Zerfa; Hassiba Bouabdesselam (Journal of Water and Environmental Nanotechnology)
The Beni Saf Water Company (BWC) desalination plant in Ain Témouchent (Algeria) uses reverse osmosis technique. This process, which is based on dense membranes operating at high pressure, produces a permeate with characteristics that exceeds the necessary requirements. However, the Reverse Osmosis (RO) technique suffers from the following limitations: high energy consumption, low water recovery and excessive fouling of membranes. We conducted this work to contribute to the study of seawater desalination by introducing another system such as Nanofiltration (NF) to reduce energy consumption and retard the fouling of RO membranes. This research study is focused on the installation of Nanofiltration membranes to desalinate seawater with a salinity of about 35mg/L, in order to protect RO membranes and reduce their fouling. NF was found to be effective for partial and selective desalination of the studied seawater in single or two stages, with lower energy consumption than RO. The ESNA1-LF-LD Nanofiltration membrane is more suitable and competitive compared to SWC4-LD for seawater desalination with a 99% removal rate of multivalent ions. It allows for partial desalination and also allows for the preparation of water for industrial use (cooling....) at twice the pressure and at higher conversion rates (90%). These characteristics provide system designers with new options to reduce the capital cost of the system as well as the operating costs.